Health related quality of life of head & neck cancer patients in the state of Sabah - Myint, Khaing Khaing; Ng Sien Kiat; Osman Ali; SS Sreetharan; Marina Bakri; Heric Corray; Rahimah Mohd Said (Universiti Malaysia Sabah, 2005)
Cancer of head and neck (HNC) has profound functional, cosmetic and emotional impact on patients. Both the disease and the treatment affect critical functions such as speech, swallowing and emotional wellbeing etc. In nasopharyngeal carcinoma, there is improved local control of the disease with higher survival rates with higher radiation dosage. The frequency and severity of complications such as pituitary hypofunction and otitis media with effusion are however increased. Our research project was started in June 2005. We surveyed a total number of 117 HNC patients, out of which 95 cases have nasopharyngeal carcinoma. The EORTe (European Organization for Research and Treatment of Cancer) Quality of life QLQ-C30 (Core Questionnaire) and EORTC QLQ-H&N35 (supplementary disease specific module) were used for the survey. The mean score for the different fimctional domains are physical function 74.8 (SE=1.8), role function 67.1(SE=2.5) • emotional function 66.8 (SE=2.4), cognitive function 67.7 (SE=2.2), social fimction 71.2 (SE=2.7)and overall quality of life 61.5 (SE=2.3). Compare to other studies, our patients show lower overall level of quality of life function. The emotional function in female is significantly lower than that of male; this is in accordance to that observed in studies from other countries. For head and neck specific module, the mean score for pain. swallowing, social eating and social contact are better than senses, speech and sexual function. Because majority of our patients suffered from nasopharygeal carcinoma, a relatively rare entity in western country series, and also most of our patients, i.e. 94% underwent radiotherapy, the results are difficult to compare. There were significant differential effects of ethnic group on the role function, emotional function. cognitive function and pain in our model. The differential effect is mainly due to the differences between Chinese and Kadazandusun. The Chinese fare better in terms of role function, emotional function. cognitive function and are less disturbed by pain when compared to the Kadazandusun. The present study has highlighted the effects of head and neck cancer on patient's quality of life. At present improvement of survival of patient remains the most important outcome in most clinical research. The results of our study also indicate the possibility of using quality of life parameters to assess treatment outcomes. Rather than just survival alone. quality of life parameters should also be included in selecting and deciding appropriate therapy for patients.